Brain Activation for Audiovisual Information in People With One Eye Compared to Binocular and Eye-Patched Viewing Controls - Moro, Stefania S.; Gorbet, Diana J.; Steeves, Jennifer K. E. (Frontiers in Neuroscience, 2020)
Blindness caused by early vision loss results in complete visual deprivation and subsequent changes in the use of the remaining intact senses. We have also observed adaptive plasticity in the case of partial visual deprivation. The removal of one eye, through unilateral eye enucleation, results in partial visual deprivation and is a unique model for examining the consequences of the loss of binocularity. Partial deprivation of the visual system from the loss of one eye early in life results in behavioural and structural changes in the remaining senses, namely auditory and audiovisual systems. In the current study we use functional neuroimaging data to relate function and behaviour of the audiovisual system in this rare patient group compared to controls viewing binocularly or with one eye patched. In Experiment 1, a whole brain analysis compared common regions of cortical activation between groups, for auditory, visual and audiovisual stimuli. People with one eye demonstrated increased activation for low-level audiovisual stimuli compared to patched viewing controls but did not differ from binocular viewing controls. In Experiment 2, a region of interest (ROI) analysis for auditory, visual, audiovisual and illusory McGurk stimuli revealed that people with one eye had increased left hemisphere audiovisual activation for McGurk stimuli compared to binocular viewing controls. This aligns with previous research showing reduced McGurk Effect in people with one eye. Together with previous behavioural work, these functional data contribute to the broader understanding of cross-sensory effects of early sensory deprivation from eye enucleation. Overall, these results contribute to a better understanding of the sensory deficits experienced by people with one eye, as well as, the relationship between behavior, structure and function in order to better predict the outcome of early partial visual deafferentation.